Upgrading the low-grade waste heat from alkaline fuel cells via isopropanol-acetone-hydrogen chemical heat pumps. (15th February 2023) - Zhu, Huichao; Zhang, Houcheng
Abstract: To upgrade the quality of low-grade waste heat, a new coupling system integrating isopropanol-acetone-hydrogen chemical heat pump (IAH-CHP) to alkaline fuel cell (AFC) is proposed. The irreversible losses in the electrochemical and thermodynamic processes are quantitatively analyzed, and the energy and exergy performance indicators of each system component and coupling system are obtained based on the steady-state mathematical models and thermodynamic laws. Numerical calculations show that the achievable peak output power density and its corresponding energy efficiency, exergy destruction rate density and exergy efficiency are, respectively, 70.95%, 25.65%, 30.84% and 25.59% greater than that of the sole AFC. Optimal operation regions for various key performance indicators are obtained. The competitiveness of the proposed system is checked by comparing it with the available AFC-based coupling systems. Furthermore, the effects of operating temperature, temperature of exothermic reaction, molar ratio of hydrogen to acetone in the exothermic reactor before exothermic reaction, reflux ratio, thermodynamic loss composite parameter and IAH-CHP regenerator effectiveness on the coupling system performance are analyzed. The results obtained in this paper may provide some theoretical bases for improving the thermodynamic performance of such practical coupling systems. Highlights: A novel chemical heat pump is proposed to upgrade alkaline fuel cell's waste heat. Performance features are revealed from energetic and exergetic perspectives. Maximum output power gains 71% improvement compared to that of a single AFC. Effectiveness and competitiveness of the proposed system are checked. Effects of some key operation conditions and design parameters are revealed.